SERVANT LEADERSHIP AND ORGANIZATIONAL COMMITMENT: THE MEDIATING ROLE OF JOB SATISFACTION - Permatasari A.A.S.I.; Riana I G. (Eurasia: Economics & Business, 2023)
The purpose of this study is to analyze the effect of servant leadership on job satisfaction and organizational commitment and analyze the mediating role of job satisfaction in the effect of servant leadership on organizational commitment. The population of this study was all employees of Tri Homestay Tuban and Tri Homestay Ungasan with a sample of 68 respondents. The sampling method uses saturated samples. The data collection methods used in this study were interviews and questionnaires. The data was analyzed by Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. The results show that servant leadership has a positive and significant effect on organizational commitment. Servant leadership has a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on organizational commitment. Job satisfaction mediates partially complementary to the effect of servant leadership on organizational commitment. The implications of the research results show that to increase employee organizational commitment, companies need to emphasize or increase the values of loyalty to employees to foster a sense of pride and remain loyal to the company as an obligation for employees.